Situation Report: Hungary, 3 July 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungary to Celebrate the Millennium of the Adoption of Christianity Anniversary of Nicolai [Nicolae] Balcescu's Birth Celebrated Hungarian-Yugoslav Economic Contacts Co-operation Agreement between Hungarian and Slovak Consumer Co-Operatives American Soldier Defects to Hungary Hungarian Echo of Nixon's Planned Visit to Romania Solzhenitsyn Highly Praised by Kortars Author (Part II) Nepszabadsag on Consolidation in Czechoslovakia